Electrical stimulation of insect leg muscles toward biological walking machine - Daniyal Haider Sangi (2013)
This report aims to provide an insight into a novel project intended to induce artificial walking protocols in a live beetle. The report consists of, in addition to an overview of the existing literature on the insect anatomy and muscle configuration, an in-depth design and evaluation of the aforementioned objective.